They Leave Their Kidneys in the Fields : Illness, Injury, and Illegality among U.S. Farmworkers - Horton, Sarah Bronwen (Book collections on Project MUSE., 2016)
"They Leave Their Kidneys in the Fields takes the reader on an ethnographic tour of the melon and corn harvesting fields in California's Central Valley to understand why farmworkers die at work each summer. Laden with captivating detail of farmworkers' daily work and home lives, Horton examines how U.S. immigration policy and the historic exclusion of farmworkers from the promises of liberalism has made migrant farmworkers what she calls 'exceptional workers.' She explores the deeply intertwined political, legal, and social factors that place Latino migrants at particular risk of illness and injury in the fields, as well as the patchwork of health care, disability, and Social Security policies that provide them little succor when they become sick or grow old. The book takes an in-depth look at the work risks faced by migrants at all stages of life: as teens, in their middle-age, and ultimately as elderly workers. By following the lives of a core group of farmworkers over nearly a decade, Horton provides a searing portrait of how their precarious immigration and work statuses culminate in preventable morbidity and premature death"--Provided by publisher.